2013 IEEE 24th Annual International Symposium on Personal, Indoor, and Mobile Radio Communications (PIMRC) 2013
DOI: 10.1109/pimrc.2013.6666556
|View full text |Cite
|
Sign up to set email alerts
|

Study on the effects of backhual solutions on indoor mobile deployment „macrocell vs. femtocell”

Abstract: the deployment of low cost and low power base stations has been recognized in recent years as a promising cost-efficient solution and energy-efficient strategy. In this paper the femtocell and macrocell deployment options have been compared in the context of indoor mobile broadband deployment, with focus on the effect of different backhauling solutions in power consumption and the total deployment cost. This study has been based on the deployment of mobile broadband services within an area of one square kilome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…A comparison of fiber-based backhaul systems with existing fiber-to-the-home solutions is presented in [21]. The economic effects of fiber and microwave backhaul systems for low and high wireless traffic requirements were investigated in [22]. In [23], the optimal deployment costs associated with different deployment scenarios and different fronthaul technologies, including Analog and Digital Radio over Fiber were analyzed.…”
Section: Related Workmentioning
confidence: 99%
“…A comparison of fiber-based backhaul systems with existing fiber-to-the-home solutions is presented in [21]. The economic effects of fiber and microwave backhaul systems for low and high wireless traffic requirements were investigated in [22]. In [23], the optimal deployment costs associated with different deployment scenarios and different fronthaul technologies, including Analog and Digital Radio over Fiber were analyzed.…”
Section: Related Workmentioning
confidence: 99%
“…The self-interference cancellation is assumed to be perfect, i.e., ρ si = Γ ij,li,f = 0. The network cost model is set following [63], [64], as W p = 1, W l = 20, W f = 10.…”
Section: Network Planning: An Milp Modelmentioning
confidence: 99%
“…The results presented in the paper show that in urban areas it is possible to reach up to 70% cost savings using indoor small cell deployments in place of traditional ones based on macro BSs. The works in [8,9] studied both homogenous and heterogeneous wireless architectures and assessed the impact of their backhaul network on the entire TCO. The results indicate that in HetNets the backhaul network represents a considerable portion of the TCO, while in homogeneous networks, based on macro BSs only, the backhaul cost does not affect significantly the TCO.…”
Section: Related Workmentioning
confidence: 99%
“…Their results showed that point-to-point microwave is a costefficient technology to provide high backhaul capacity in short deployment times. Moreover, the authors in [4,8,11,12] assessed the Capital Expenditure (CAPEX) and Operational Expenditure (OPEX) of mobile backhaul networks in several Greenfield deployment scenarios. More specifically, paper [8] assessed the economic impact of fiber and microwave backhaul solutions in the presence of low and high wireless capacity demands, while paper [11] compared the cost of different backhaul deployments based on fiber and copper in a scenario where fixed broadband access is already provided using fiber to the node solutions.…”
Section: Related Workmentioning
confidence: 99%